Expressão de microRNAs envolvidos com o crescimento muscular do pacu (Piaractus mesopotamicus): análises in vivo e in vitro - Duran, Bruno Oliveira da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Pacu (Piaractus mesopotamicus) is a Brazilian fish with high economic interest for pisciculture due to features such as rusticity and fast growth. Postnatal growth of skeletal muscle in fish occurs by hyperplasia and/or hypertrophy, processes that are dependent on the proliferation and differentiation of myoblasts. A class of small noncoding RNAs, known as microRNAs (miRNAs), represses the expression of target mRNAs, and many studies demonstrate that miR-1, miR-133, miR-206 and miR-499 regulate different processes in skeletal muscle through the mRNA silencing of HDAC4, SRF, Pax7 and Sox6, respectively. The aim of our work was to evaluate the expression of miRNAs and their putative target mRNAs in fastand slow-twitch skeletal muscle of pacu during growth. Our results revealed an inverse correlation between the expression of miRNAs and their target mRNAs, and there was evidence that miR-1, miR-133 and miR-206 may regulate the proliferation and differentiation of myoblasts. On the other hand, miR-499 was highly expressed in slow-twitch muscle, which suggests its involvement in the specification and maintenance of the slow phenotype in muscle fibres. miRNA expression exhibited variations between different development stages and between distinct muscle twitch phenotypes. This work provided the first identification of miRNA expression profiles related to skeletal muscle in pacu and suggests an important role of these molecules in this tissue

O pacu (Piaractus mesopotamicus) é um peixe brasileiro que apresenta elevado interesse econômico para a piscicultura, devido a características como rusticidade e rápido crescimento. O crescimento pós-natal do músculo esquelético em peixes ocorre por hiperplasia e/ou hipertrofia, processos dependentes da proliferação e diferenciação de mioblastos. Uma classe de pequenos RNAs não codificantes, conhecidos como microRNAs (miRNAs), reprime a expressão de mRNAs alvo, e muitos estudos mostram que o miR-1, miR-133, miR-206 e miR-499 regulam diferentes processos no músculo esquelético pelo silenciamento da HDAC4, SRF, Pax7 e Sox6, respectivamente. O objetivo do nosso trabalho foi avaliar a expressão dos miRNAs e de seus supostos mRNAs alvo nos músculos esqueléticos de contração rápida e lenta do pacu durante o crescimento. Nossos resultados mostraram uma correlação inversa entre a expressão dos miRNAs e de seus mRNAs alvo, e houve evidências de que o miR-1, miR-133 e miR-206 podem regular a proliferação e diferenciação de mioblastos. Por outro lado, o miR-499 foi altamente expresso no músculo de contração lenta, sugerindo seu envolvimento na especificação e manutenção do fenótipo lento nas fibras musculares. A expressão dos miRNAs mostrou variações entre diferentes estágios de desenvolvimento e entre fenótipos de contração muscular distintos. Esse trabalho forneceu a primeira identificação do perfil de expressão de miRNAs relacionados ao músculo esquelético no pacu e sugere um importante papel dessas moléculas nesse tecido
Keywords: Expressão gênica; Regulamento genetico; Sistema musculoesquelético; Pacu (Peixe); Musculoskeletal system; Fishes